Trajectories of exposure and vulnerability of small islands to climate change. (31st May 2017) - Duvat, Virginie K.E.; Magnan, Alexandre K.; Wise, Russell M.; Hay, John E.; Fazey, Ioan; Hinkel, Jochen; Stojanovic, Tim; Yamano, Hiroya; Ballu, Valérie
Abstract : This article advocates for a dynamic and comprehensive understanding of vulnerability to climate‐related environmental changes in order to feed the design of adaptation future pathways. It uses the trajectory of exposure and vulnerability (TEV) approach that it defines as 'storylines of driving factors and processes that have influenced past and present territorial system exposure and vulnerability to impacts associated with climate variability and change.' The study is based on the analysis of six peer‐reviewed Pacific island case studies covering various geographical settings (high islands vs low‐lying reef islands, urban vs rural) and hazards associated with climate variability and change; that addressed the interactions between natural and anthropogenic driving factors; and adopted multidecadal past‐to‐present approaches. The findings emphasize that most urban and rural reef and high islands have undergone increasing exposure and vulnerability as a result of major changes in settlement and demographic patterns, lifestyles and economies, natural resources availability, and environmental conditions. The article highlights three generic and successive periods of change in the studied islands' TEV: from geopolitical and political over the colonization‐to‐political independence period; to demographic, socio‐economic, and cultural from the 1960s to the 1980s; culminating in the dominance of demographic, socio‐economic, cultural, and environmental drivers since the 1980s. Based on these empirical insights, the article emphasizes the existence of anthropogenic‐driven path‐dependency effects in TEV, thus arguing for the analysis of the temporal dimensions of exposure and vulnerability to be a prerequisite for science to be able to inform policy‐ and decision‐making processes toward robust adaptation pathways. WIREs Clim Change 2017, 8:e478. doi: 10.1002/wcc.478 This article is categorized under: Climate and Development > Social Justice and the Politics of Development Abstract : South Tarawa atoll, Kiribati (credit: V.K.E. Duvat) The South Tarawa Urban District (STUD), stretching 35 km on the southern rim of Tarawa Atoll in Kiribati (Central Pacific), experienced a dramatic increase in its Trajectory of Exposure and Vulnerability (TEV) to climate‐related hazards over the last decades to century, mainly due to the centralization of political power, key services and work opportunities, and to population growth, which have all together caused widespread environmental degradation. More generally, it illustrates the processes at work in Pacific atolls' urban districts and islands. This article advocates for a temporal and comprehensive understanding of the main drivers of TEV to climate‐related environmental changes so as to capture latency phenomena in social systems and related path‐dependency effects. The paper then concludes for the TEV approach to be a pre‐requisite for science to be able to inform policy‐ and decision‐making processes towards robust adaptation pathways.